CEREBROVASCULAR ACCIDENT AS A RISK FACTOR FOR URINARY INCONTINENCE IN HOSPITALIZED ELDERLY PEOPLE - Quadros, Layse Biz (2017)
Risk factors (age, gender, co-morbidities/life style, walking capacity, cognitive decrease and occurrence of Cerebrovascular Accident) in elderly with urinary incontinence and hospitalized in a home are analyzed by a descriptive and transversal research with 76 elderly people. The occurrence of urinary incontinence by the Incontinence Questionnaire and the occurrence of Cerebrovascular Accident by clinical assessment were investigated. Profile analysis of clinical charts, cognition and functionality was undertaken by Mini-Test of Mental Conditions and Barthel´s Index and the functional conditions after Cerebrovascular Accident by Rankin´s Scale (modified) were determined. Urinary incontinence occurred in 37,10% of the elderly, with a prevalence in elderly suffering from CVA (p=0,002). Walking (p=0,000), cognition (p=0,003) and occurrence of CVA (p=0,002) were associated to urinary incontinence. Results show that reduced walking capacity is associated to the development of urinary incontinence in elderly with CVA in care homes.